IDENTIFICATION OF SECONDARY METABOLITES COMPOUNDS, ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES ON THE METHANOL EXTRACT OF SEA CUCUMBER Stichopus hermanii - Abdullah Rasyid (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Identification of secondary metabolites, antibacterial and antioxidant activities assay of methanol extract of sea cucumber Stichopus hermanii were conducted from May to July 2011 at the Natural Products Laboratory, Research Center for Oceanography, Indonesian Institute of Sciences. Sea cucumber used in this study comes from South Lampung waters. Objective of the study was to get information of secondary metabolites, antibacterial and antioxidant activities of methanol extract of sea cucumber S. hermanii. The extraction method which used in this experiment was the maceration method using methanol solvent. Identification of secondary metabolites was performed through observing reaction of colors, precipitation, and foaming. Antibacterial and antioxidant activities of methanol extract from sea cucumber were tested using agar diffusion method and reducing of free radicals 1.1-Diphenyl-2-Picrylhydrazyl (DPPH) respectively. The results showed that secondary metabolites identified in the methanol extract of sea cucumber S. hermanii were saponin and steroids. Both secondary metabolites had antibacterial activities against Staphylococcus aureus, Vibrio eltor and Bacilus subtilis. The analysis of antioxidant activity showed that the IC50 value of methanol extract of sea cucumber S. hermanii was about 65.08 ppm. It indicated that S. hermanii is having potency as antibacterial and antioxidant. Keywords: antibacterial, antioxidants, sea cucumber Stichopus hermanii, secondary metabolites